Two new species of the genus Hamataliwa Keyserling, 1887 (Araneae: Oxyopidae) from Gaoligong Mountains, Yunnan, China - Tang, Guo; Wang, Qiaobing; Peng, Xianjin (Zootaxa, 2012)
Two new species of the genus Hamataliwa (Araneae: Oxyopidae) from the Gaoligong Mountains area, Yunnan Province,China are described: Hamataliwa cucullata sp. nov. (male, female) and Hamataliwa torsiva sp. nov. (female). Photos of the morphological appearances and illustrations of the genital organs are provided.